A tool for designing and evaluating the temporal work patterns of human and artificial agents - Gladden, Matthew E. (Business Informatics, 2014)
The measure of availability that is often used to compare the dependability of computer-based systems is imperfect, insofar as two systems with the same availability can display quite different performance characteristics. Here we develop a new fractal temporal measure for work effort that offers insights into a system’s performance not captured by the traditional availability measure. Moreover, we show that this fractal measure can be used to compare the temporal work patterns of both human and artificial agents and identify their unique strengths and weaknesses. Such new comparative tools will become increasingly important as the development of more sophisticated artificial agent technologies creates situations in which particular functions within an organization can be carried out either by human or artificial personnel
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 61-76
Keywords: Performance analysis; fractal dimension; management of computing and information systems; working hours; artificial intelligence (incl. robotics); analiza wydajności; wymiar fraktalny; zarządzanie obliczeniami i systemami informacji; godziny pracy; sztuczna inteligencja (łącznie z robotyką)